Management Strategies of Saint Gabriel Foundation’s Schools in Thailand According to The Concept of Enhancing Digital Citizenship in Students - Sakonthawat, Seksan; Viseshsiri, Pongsin; Siribanpitak, Pruet (Scholar: Human Sciences, 2018)
The objectives of this research were 1) to explore the conceptual framework of management strategies of Saint Gabriel Foundation’s schools in Thailand according to the concept of enhancing digital citizenship; 2) to explore the current and desirable statuses of the management strategies of these schools; and 3) to develop the management strategies of these schools. The research applied a mixed methods research approach. The population included 16 Saint Gabriel Foundation’s schools in Thailand in academic years 2017. The instruments comprised a concept questionnaire; a current and desirable statuses questionnaire; and an assessment form for the propriety and feasibility of management strategies. The data analysis involved descriptive statistics, i.e. frequency, percentage, mean, and standard deviation; PNIModified indices; and content analysis. The results revealed that the conceptual framework of enhancing digital citizenship in students encompassed 3 components including the respect toward oneself and others in digital world; the use of digital appliances with responsibility and safety; and digital innovations creation. Internal status analysis indicated academic department as weakness and student affairs department as strength; and external status analysis indicated government policy, economic status, and social status as threats, and technology as opportunity. The management strategies of Saint Gabriel Foundation’s schools in Thailand according to the concept of enhancing digital citizenship comprised 3 main strategies, namely: (1) To improve school management to enhance students’ digital responsibility and safety; (2) To enhance management capacity to develop students’ ability to create digital innovations; and (3) To uplift school management to enhance students respect in themselves and others in the digital world.